Violências entre pares no contexto escolar: razões e enfrentamentos - Britto, Éder Soares Sá (2019)
The purpose of this research is to analyze the school violence that occurred among students. It is assumed that the actions of violence between peers are the result of conflicts existing in the school space. We seek to answer the following questions: How does violence occur in school? With a view to overcoming the conflicts that generate the violence between peers, would there be at school a space for dialogue? It has as general objective to understand the phenomenon of violence at school developed among high school students. The specific objective was to characterize the school and the subjects participating in the research; identify and analyze the causal factors of violence in schools and its consequences; analyze the manifestations of conflicts that generate violence and find in school a possibility for dialogue. The research universe is a state public school located in a region of socio-spatial segregation in the city of São Paulo. The subjects of the survey were regular high school students who experienced conflicts and, as a consequence, acts of violence. The methodology used was of qualitative character, whose data collection instruments were questionnaire applied to 100 high school students; study of the book of school occurrences; discussion of the results; attentive observation, stages of epistemological circles. The methodology was aimed at stimulating students' critical awareness of violence practices and presenting dialogue as an instrument of conscientious intervention. As a result of the research, students were systematized a set of codes of school relations based on the dialogue and awareness of school children focused on coping with violence in the school context. The pedagogical intervention proposal was delivered to the school in order to assist it in its actions to overcome the violence. The work took a qualitative approach to the case study. The research took place between the years 2017 and 2018 with the theoretical contribution of the Freirean perspectives in dialogue with other authors of education.